2019
DOI: 10.3906/vet-1811-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and phylogenetic analysis of the honeybee (Apismellifera) sacbrood virus in Turkey

Abstract: Sacbrood virus (SBV) is widely distributed in honeybees. It is an infectious and contagious disease, which affects both the larvae and adult stages of honeybees (Apis mellifera). This study reports the detection of sacbrood virus in Turkey in 2017. Phylogenetic analysis based on partial sequences encoding the polyprotein gene was carried out in SBV-infected bees from four different apiaries. Phylogenetic analysis revealed noteworthy results. Although European-South American, Asian, and Korean genotypes have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…This range can be explained by the fact that CBPV is a segmented and variable virus. In addition, the genomic variability of honeybee viruses, such as the Sacbrood virus in Turkey has been previously described (Kalayci et al, 2019;Yildirim et al, 2020). The genetic variability of CBPV was also reported in a previous study by Cagirgan (2018).…”
Section: Resultssupporting
confidence: 55%
“…This range can be explained by the fact that CBPV is a segmented and variable virus. In addition, the genomic variability of honeybee viruses, such as the Sacbrood virus in Turkey has been previously described (Kalayci et al, 2019;Yildirim et al, 2020). The genetic variability of CBPV was also reported in a previous study by Cagirgan (2018).…”
Section: Resultssupporting
confidence: 55%
“…Numerous studies have been performed on bee viruses in Turkey in the past (14,17,18,23,35,42). In these studies, it was reported that the incidence of DWV was high in certain regions in Turkey (24,42).…”
Section: Resultsmentioning
confidence: 99%
“…Although there have been numerous colony losses throughout the world, the reasons for which are mainly unknown, one of the principal factors that leads to colony loss is viruses. For this reason, bee viruses have been the subject of many different studies conducted in Turkey (14,17,18,23,35,42).…”
mentioning
confidence: 99%
“…Karapınar et al (2018) detected four viruses (ABPC, CBPV, DWV, BQCV) in Van honey bees [19]. Kalaycı et al (2019) detected SBV in honey bees from Muğla province [46]. Rüstemoglu and Sipahioglu (2019) defined 6 viruses (BQCV, DWV, SBV, CBPV, KBV, IAPV) in honey bees in Hakkari province [15].…”
Section: Discussionmentioning
confidence: 99%